Compression properties of multifunctional composite structures with embedded lithium-ion polymer batteries. (1st April 2020) - Attar, P.; Galos, J.; Best, A.S.; Mouritz, A.P.
Abstract: Multifunctional light-weight composite structures that combine high load-bearing properties with electrical energy storage capacity have potential application in energy intensive systems such as electric cars. This paper examines the effect of compression loading on the mechanical and electrical responses of light-weight carbon fibre laminates containing embedded lithium ion polymer (LiPo) batteries. The mechanical and electrical responses of the LiPo battery itself to compression loading are also examined. Embedding batteries has a significant adverse effect on the compressive stiffness, failure stress and fatigue life of laminates. The property reductions are attributed to several factors; namely the compressive properties of the battery being much lower than the composite material, the geometric stress concentration created by the battery, discontinuities in the carbon fibres, and the soft polymer layer at the battery-composite interface that effects load transfer. Experimental testing and finite element analysis reveal that the reduction to the compression properties is dependent on the number and arrangement of the batteries.